HUBUNGAN ANTARA KEPEMILIKAN BUKU KIA DENGAN PENGETAHUAN, SIKAP DAN PRAKTIK PERAWATAN KEHAMILAN DI WILAYAH KERJA PUSKESMAS RANGKAH SURABAYA - Kusindijah, Kusindijah (EMBRIO, 2012)
The Indonesian Statistic Board notes in 2007, the incidence of maternal mortality rate (248/100.000 live birth) places Indonesia as the highest in Southeast Asia. In collaboration with JICA, the Health Ministry has developed and implemented MCH book on the purpose of improving mother and baby health status. This study intended to identify the association between the ownership of MCH and knowledge, attitude and practices of mother on prenatal care. It is an analytical study using cross sectional approach. The study conducted in Puskesmas Rangkah Surabaya starting August to November 2010. Random sampling procedure was used to select 88 samples. While MCH book ownership is the independent variable, knowledge, attitude and practices on prenatal care is the dependent one. The study reveals that there is no significant relation between independent variable and mother’s knowledge (p=0.748 >0.05); attitude (p=0.655 >0.05) and prenatal cares (p= 0.195> 0.05).